Optimization of Drilling Sample Handling in Laterite Nickel Exploration in Central Sulawesi - Gunawan, Risal; Prianata, Yogi Laode; Rinaldi, Ahmad Jeli; Joaques, Juan (Lembaga Penelititan dan Pengabdian kepada Masyarakat - Institut Teknologi Adhi Tama Suraba, 2025)
The exploration of lateritic nickel in Indonesia plays a crucial role in meeting the demands of the electric vehicle battery and stainless-steel industries. One of the critical aspects of exploration is proper handling of drilling samples to ensure the accuracy of geochemical and mineralogical data. PT. Cakrawala Resources Indonesia has implemented standard procedures for sample management at the Sambalagi Site. However, challenges remain regarding storage, transportation, and quality control, which may affect the integrity of exploration data. The purpose of this research study was conducted using a field study approach and technical analysis of sample handling procedures, covering site preparation, drilling, and storage in the sample house. The evaluation was carried out by observing the effectiveness of each stage and identifying factors that could potentially cause sample degradation. Additionally, a review of quality control system implementation was conducted, including sample duplication methods and blind sampling. The research results indicate that the applied sample handling methods comply with exploration standards. However, challenges remain, such as high humidity conditions that can affect sample quality and difficult-to-access terrain that may hinder transportation processes. While quality control measures have been implemented, optimization is still needed in record-keeping and storage to enhance data traceability. Improvements in sample house storage conditions, sample transportation optimization, and the implementation of a digital recording system are recommended to enhance exploration efficiency and accuracy.